ANALISIS KOMODITAS UNGGULAN HORTIKULTURA DI KABUPATEN OKU - Wika Asmaga; Fifian Permata Sari; Rini Efrianti (LPSDI Bina Patria, 2025)
Horticulture plays an important and strategic role and occupies a strategic position in the development of the Indonesian agricultural sector because of its role as a major component in the expected food pattern. This research will be conducted at PT BPR This research was conducted in OKU Regency. The determination of the location was carried out intentionally (Purposive) considering OKU Regency. To answer the first problem above, using the mix method analysis technique, combining quantitative analysis and qualitative analysis to support the achievement of final results or strategies (Sugiyono, 2020). Data analysis uses Location Quotient (LQ), and Shift Share in determining superior commodities. Based on the results of the study, the superior commodities of the horticulture sub-sector that can be developed using LQ analysis in OKU Regency are as follows, shallots, large chilies, cayenne peppers, tomatoes, eggplants and spinach with an LQ value> 1 are the base sectors. Meanwhile, based on the Shift Share analysis, the commodities that have progressed are large chilies, cayenne peppers, tomatoes, cucumbers and spinach with a shift share value of H> 1, meaning that these commodities have progressed and can meet needs.